How Are Strategy and Organizational Culture Related? A Conceptual Discussion - Alpay, Guven; Buyukbalci, Pinar; Dulger, Meral (SPRINGER INTERNATIONAL PUBLISHING AG, 2018)
This paper seeks to foster a conceptual discussion about the relationship between organizational culture and strategy. Organizations must find ways to handle global, national, market, technological and consumer demands whilst crafting relevant strategies to their internal workings and cultures. When the strategies of organizations are misaligned with market realities, the survival rate rapidly decreases. We suggest that the culture of organizations offer an anchor dictating how organizations perceive themselves, their surroundings, their customers and relevant stakeholders. The assumptions, beliefs and values determine how companies comprehend what is happening inside and outside the organization while dominating the strategy formulation and execution process. In a culture where change is avoided, prompt adaptation to market changes could be painful if not impossible. Thus, we propose that organizational culture can be utilized as a bridge for aligning inner realities of organizations with demands of the outer domain. Essentially, we suggest that organizations' internal values and culture are generally not aligned with their strategic positions and that the focus of organizations need to be on a fit which will create a competitive cultural persona supporting the strategic posture in the marketplace. Such a fit will enable organizations to deploy resources effectively and manage information flow smoothly.
Keywords: Strategy; Organizational culture; Competitiveness; New economy; Organizational structure; AMBIDEXTERITY; Business & Economics